"Saudades" and returning: brazilian women speak of here and there (Tempo e Argumento, 2010)
This article explores the concept of returning to Brazil articulated by a small group of Brazilian women living in Boston, MA, area. The time each of the women spent in the United States varies considerably. In the interviews they talked about whether they had plans to return to Brazil, and, in this paper, we examine the relationship between their conception of saudade, their transnational experience and their desire to return to their homeland. We look specifically at three subsets of women: women who planned to stay in the U.S. permanently; women who said their stay in the U.S. was temporary; and women who were unsure of whether they would stay or leave. This article uses excerpts from the women’s stories to illustrate the relationship between the idea of returning to Brazil, the idea of saudade and the transnational status.
Keywords: brazilian immigrant women; return to Brazil; transnational; immigration